ANALISIS HUKUM EKONOMI SYARIAH KOMPETENSI, INDEPENDENSI DAN PROFESIONALISME TERHADAP KINERJA AUDIT INSPEKTORAT DALAM PENGAWASAN KEUANGAN DAERAH DI KOTA MAKASSAR - Andi Gunawan Ratu Chakti (Al-Amwal : Journal of Islamic Economic Law, 2021)
This study aims to examine the effect of competence, independence, and professionalism on the performance of the regional inspectorate apparatus and examine the auditor's compliance with the Professional Standards of Public Accountants (SPAP). The general problem in this study is that the audit findings were not detected by the inspectorate apparatus as internal auditors, but were found by the external auditor, namely the Supreme Audit Agency (BPK). Operationally, research variables are described in several indicators. The variable of apparatus competence is translated into three indicators, namely mastery of accounting and auditing standards, governance insights, and skills improvement programs. The variable of apparatus independence is translated into two indicators, namely personal disturbances and external disturbances. The variable of apparatus professionalism is translated into four indicators, namely: dedication to the profession, social obligation, independence, and confidence in the profession. The audit performance variable is translated into four indicators, namely: process quality, result quality, and audit follow-up.The population of this research is Makassar City Regional Inspectorate apparatus who follow periodic inspections. Data were collected from questionnaires distributed to respondents. The variables in this study are independent variables (X1), independence (X2) and professionalism (X3), while the dependent variable is audit performance (Y). Data were analyzed using multiple linear regression analysis (multiplerepression).The results showed that competence and professionalism had a positive and significant effect on audit performance, while the independence variable had no significant effect on audit performance. The coefficient of determination shows that competence, independence, and professionalism together contribute to the dependent variable (audit performance) of 72.2%, while the remaining 27.8% is influenced by other factors outside the model. The implication of the findings of this study on efforts to realize a quality audit is the need for professionalism to auditors regarding the urgency of a quality audit in addition to efforts to increase competence through training.